2014
DOI: 10.1128/jvi.00381-14
|View full text |Cite
|
Sign up to set email alerts
|

NTPDASE4 Gene Products Cooperate with the Adenovirus E4orf4 Protein through PP2A-Dependent and -Independent Mechanisms and Contribute to Induction of Cell Death

Abstract: The adenovirus E4orf4 protein induces nonclassical apoptosis in mammalian cells through at least two complementing pathways regulated by the interactions of E4orf4 with protein phosphatase 2A (PP2A) and Src kinases. In Saccharomyces cerevisiae cells, which do not express Src, E4orf4 induces PP2A-dependent toxicity. The yeast Golgi apyrase Ynd1 was found to contribute to E4orf4-mediated toxicity and to interact with the PP2A-B55␣ regulatory subunit. In addition, a mammalian Ynd1 orthologue, the NTPDASE4 gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Cell death assay: the DAPI assay. DAPI assays, which determine nuclear aberrations, have been described previously (68,69). Briefly, cells were transfected with plasmids expressing E4orf4.…”
Section: Fig 11mentioning
confidence: 99%
“…Cell death assay: the DAPI assay. DAPI assays, which determine nuclear aberrations, have been described previously (68,69). Briefly, cells were transfected with plasmids expressing E4orf4.…”
Section: Fig 11mentioning
confidence: 99%
“…The knockdown of NTPDASE4 suppressed E4orf4 induced cell death while overexpression enhanced E4orf4-induced cell killing. Study findings suggest that the E4orf4-NTPDase4 pathway, partly in association with PP2A, may provide an alternative mechanism to contribute to the cytoplasmic death function of E4orf4 [166].…”
Section: Subcellular Localization and Mechanism Of Action: Cytoplasmimentioning
confidence: 99%
“…Cabon et al [165] added that arrested cells died due to accumulation of both diploid and tetraploid cells, which are unable to initiate DNA synthesis. Recently, Avital-Shacham et al [166] reported that the NTPDASE4 gene product Gogi UDPase, a mammalian orthologue of yeast Ynd1, interacts with E4orf4. The knockdown of NTPDASE4 suppressed E4orf4 induced cell death while overexpression enhanced E4orf4-induced cell killing.…”
Section: Subcellular Localization and Mechanism Of Action: Cytoplasmimentioning
confidence: 99%
“…However, when expressed alone at high levels, E4orf4 induces the selective p53-independent death of a variety of human tumor cells (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and is toxic in the yeast Saccharomyces cerevisiae (22)(23)(24)(25)(26)(27)(28)(29). Killing of cancer cells by E4orf4 is dose dependent and resembles apoptosis in some cell lines, but it seems to occur by mitotic catastrophe in others (8-13, 15, 30, 31).…”
mentioning
confidence: 99%
“…To date, several E4orf4 interacting partners besides PP2A have been reported and, in some cases, suggested to contribute to E4orf4-induced cell death, including c-Src (12,18,31,(70)(71)(72)(73)(74), the ATP-dependent chromatin-remodeling factor ACF (3), the NTPDASE4 gene product Golgi UDPase (20,29), and Nup 205 (2). In an attempt to discover more E4orf4 binding partners, we performed affinity purification/mass spectrometry (AP-MS) using both wild-type E4orf4 and class I and class II E4orf4 mutants.…”
mentioning
confidence: 99%